PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT DI RUMAH SAKIT SELE BE SOLU KOTA SORONG - Janet Lian Kaikatui; Andrey Maryen; Lili Sarce Joi Sapari (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the effect of service quality on community satisfaction at Sele Be Solu Hospital, Sorong City. This type of research is quantitative. This research was conducted at Sele Be Solu Hospital, Sorong City, from 18 May to 20 May 2022. The research sample consisted of 60 respondents. There are 2 sources of data used, namely primary data and secondary data. The data collection technique used is a questionnaire. The data analysis technique used is simple linear regression analysis test, t-test, and coefficient of determination test. The results show that the calculation of the simple regression coefficient above shows the value of the constant coefficient of 6.080, the coefficient of the independent variable (X) is 0.628. So that the regression equation Y=6.080+0.628X is obtained, the t-count value is greater than the t-table value, namely 6.706 > 4.293 with a significance level of 0.000 <0.05, and the adjusted R square value is 0.427 or 42.7%. This means that service quality has an effect on community satisfaction in Sele Be Solu Hospital, Sorong City 42.7%.